PVACLAMP: Portable Vacuum Clamping for Tool Room / Norfariza Ab Wahab … [et al.] - Ab Wahab, Norfariza; Nordin, Abd Khahar; Ibrahim, Mohd Azimin; Mohd Najib, Suhaila; Lisa Matius, Jacob (Division of Research and Industry Linkages, 2017)
Clamping tool has an ability to hold an object securely through inward pressure to prevent movement or separation. Therefore, this tool is significant in cutting process. Conventional clamping methods in machine are universal angle milling vise and plain milling machine vise. Limitations occur in conventional method such as restriction in clamping complex shape, time consuming and provide non-uniform pressure or force towards work piece. Therefore, vacuum clamping method has been introduced to overcome this problem. This project is to propose a new design and develop of portable vacuum clamping for tool room. Mild steel has been chosen to be the main material for the vacuum clamping because it is harder and cheaper than other material in the market. CATIA V5 software has been used to design the overall product. This vacuum clamping device consists of two parts. Part 1 is vacuum clamping with dimension is 132mm (width) x 132mm (length) x 25mm (height) and part 2 is the vacuum pump. The vacuum pump in this project is single-staged vacuum pump VE115N with 0.47 bar suction force. Which combination of both parts makes it portable to be attached in any machine in example drilling, milling and grinding machine. To evaluate the product reliability, experiments have been conducted to measure surface roughness after cutting process using vacuum clamping and conventional vise. The result shows that vacuum clamping has almost 50% lower roughness average (Ra) than conventional vise. For that reason, the proposed design method for overcoming the limitations of conventional clamping method has been achieved.